2023
DOI: 10.1097/ju.0000000000003389
|View full text |Cite|
|
Sign up to set email alerts
|

Ureteral Stent Placement Prior to Definitive Stone Treatment Is Associated With Higher Postoperative Emergency Department Visits and Opioid Prescriptions for Youth Having Ureteroscopy or Shock Wave Lithotripsy

Abstract: Study Need and Importance: Ureteral stents cause pain and urinary symptoms for most patients; however, the impact of ureteral stents among pediatric patients undergoing kidney stone surgery is poorly understood. We determined the association between ureteral stents and emergency department (ED) visits and opioid prescriptions for youth having ureteroscopy or shock wave lithotripsy (SWL) to improve the evidence base that informs clinical decision-making for the rapidly growing population of patients with early-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Tasian et al (page 1194) from Children’s Hospital of Philadelphia, Philadelphia, Pennsylvania, used aggregated electronic heath record data from 6 children’s health systems in North America to study the impact of primary ureteral stents on individuals 0-24 years having ureteroscopy (URS) or shock wave lithotripsy (SWL). 3 Primary ureteral stents included pre-stenting within 60 days prior to URS/SWL or concurrent stent placement. The authors found that in 2,093 patients with 2,477 surgical episodes (2,144 URS, 333 SWL) primary ureteral stent placement was associated with a higher number of emergency department visits and opioid prescriptions.…”
Section: Ureteral Stent Placement Prior To Definitive Stone Treatment...mentioning
confidence: 99%
“…Tasian et al (page 1194) from Children’s Hospital of Philadelphia, Philadelphia, Pennsylvania, used aggregated electronic heath record data from 6 children’s health systems in North America to study the impact of primary ureteral stents on individuals 0-24 years having ureteroscopy (URS) or shock wave lithotripsy (SWL). 3 Primary ureteral stents included pre-stenting within 60 days prior to URS/SWL or concurrent stent placement. The authors found that in 2,093 patients with 2,477 surgical episodes (2,144 URS, 333 SWL) primary ureteral stent placement was associated with a higher number of emergency department visits and opioid prescriptions.…”
Section: Ureteral Stent Placement Prior To Definitive Stone Treatment...mentioning
confidence: 99%